ANALISIS DETERMINAN PENERTIBAN BARANG MILIK NEGARA (STUDI PADA KANTOR PELAYANAN KEKAYAAN NEGARA DAN LELANG SEMARANG TAHUN 2007-2010) - , Anung Sita Pratiwi, Dr. Soeratno, M.Ec. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Fixed asset as a part of countryâs wealth become one of the basic capital for sustainable development requires a serious management. Good governance from the perspective of administrative, physical and legal is a manifestation of an effective, efficiency and create add value management of state asset. Governmentâs effort to achieve these goals done by rolling reforms in management of state asset such as deregulation of the rules in state asset management, restructuring the organization by the formed of Directorate General of State Wealth (DJKN) as an asset manager and carry out control of state asset. The research focused on the procces control of state asset which includes asset stocktaking, asset valuation, asset certification and reporting performed in the working area of KPKNL Semarang as vertical agency of DJKN. Data used are secondary data from the Final Report on state asset control and primary data using purposive sampling technique with a sample of 40 respondents in KPKNL Semarang. Variabel used are asset stocktaking, asset valuation, asset certification and reporting. All variables were measured using five likert scaling score. These research found several constrain encountered in procces of state aset control include lack of human resources with a knowledge about the important role of state asset enforcement regulation, lack of application skill, lack of coordination between the parties involved in regulating state asset both internally and externally, regulations that have not comprehensif, domination state asset by unauthorized parties, variation type of state asset, and limited funds. Government require follow up of state asset control to solve these problem.